Quality Control Analysis of a Digital Printing Company Based on Production Reject Data Using the C-Chart & Pareto Chart Methods - Angela Michelle; Aurelia Giza; Selvia Selvia; Uriel Christabella Valencia; Tony Michelle; Aurora Natasha; Hendriani Concetta Tiara Regina; Nurhayati Nurhayati (Yayasan Pendidikan Tanggui Baimbaian, 2026)
Digital printing industries face persistent quality challenges due to production defects that increase operational costs and reduce customer satisfaction. This study analyzed reject rates at PT. X, a mid-sized digital printing company in Tangerang, Indonesia, from August 2025 to January 2026 using quantitative descriptive-analytical methods through a case study approach. Total sampling captured 180 daily observations of production defects categorized into machine-related issues, packaging defects, lamination failures, base-support problems, blurry printing, and others. Statistical Process Control techniques employed c-charts to establish control limits (CL=1,500, UCL=1,616, LCL=1,384) and Pareto charts to prioritize dominant defect causes. Results revealed process stability for four months, with significant deviations in November 2025 (1,767 defects exceeding UCL) and August 2025 (1,327 defects below LCL), indicating special cause variations. Machine-related defects consistently contributed 40-50% of total rejects across all months. Findings confirm average reject rates of 2-3% per batch and recommend prioritizing machine maintenance and process monitoring. This research provides an adaptive SPC model for seasonal defect management in tropical manufacturing contexts and practical improvement strategies for digital printing SMEs.